2019
DOI: 10.1016/j.crad.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of mechanical thrombectomy with stent-retrievers in anticoagulated patients with anterior circulation stroke

Abstract: To assess the safety and efficacy of mechanical thrombectomy (MT) with stentretrievers in anterior circulation stroke (ACS) patients due to the occlusion of major cerebral arteries, and to compare the results achieved in patients on oral anticoagulation (OAC) and those not on OAC. MATERIALS AND METHODS: The present retrospective study comprised 285 consecutive patients (115 males; mean age 74AE13 years). The following data were collected: baseline characteristics, occurrence of risk factors, pre-event treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
6
2
Order By: Relevance
“…We found that therapeutic anticoagulation in AF patients at the time of stroke did not adversely influence outcome. This finding is similar to several studies, including thrombolysis-ineligible patients [23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…We found that therapeutic anticoagulation in AF patients at the time of stroke did not adversely influence outcome. This finding is similar to several studies, including thrombolysis-ineligible patients [23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…In general, other published studies [ 2 , 5 , 9 , 16 , 21 , 22 ] and our own data did not support this observation: in our patients, neither VKA nor NOAC intake on admission increased mortality on d90 after MT. These findings on the mortality rate are in accordance with the published ICH rates as a safety parameter that did not seem to be higher among the OAC patients as in our cohort although reported differentially detailed [ 2 , 5 , 9 11 , 14 , 16 , 17 , 19 , 21 , 22 ]. Interestingly, the multicenter observational cohort study that had already reported on increased mortality among VKA patients also found increased rates of symptomatic intracranial hemorrhage among these patients which might at least explain the higher mortality rates [ 13 ].…”
Section: Discussioncontrasting
confidence: 93%
“…Our analysis comprises the highest number of patients with 6173 in total and 1306 OAC patients compared to the recently published studies with a total number of patients ranging from 28 to 1913 and a number of OAC patients ranging from 26 to 320 [ 2 , 5 , 9 17 , 19 , 21 , 22 ]. Most studies published retrospectively collected data, but four studies were prospective cohort studies [ 2 , 5 , 9 17 , 19 , 21 , 22 ]. With regards to technical efficacy of ET, if reported, all studies showed similar reperfusion rates in OAC and non-OAC patients as in our GSR-ET cohort [ 2 , 5 , 9 , 11 , 16 , 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The recanalisation of large vessels with mechanical thrombectomy (MT) using stent retrievers is an alternative option to intravenous alteplase, which is widely used, especially for selected AIS patients. 3,4 Potential complications of MT, such as intracerebral haemorrhage (ICH) and particularly symptomatic ICH (sICH), need to be taken into consideration. sICH could have severe consequences for the AIS patient and could occur within 24e72 hours after the operation.…”
Section: Introductionmentioning
confidence: 99%